The Effects of Learning Activities in Mathematics on Probability Using Constructivist Theory with the Cooperative Learning: STAD for Matthayomsuksa 3 Students - Prongkhonburi, Jantima (Ratchaphruek Journal, 2022)
This quasi-experimental research aimed to study the effect of learning activities of mathematics subject entitled Probability based on Constructivist Theory with STAD technique for Mathayomsuksa 3 student. The purposes of this research were to: (1) Study the effects of learning activities designed to satisfy the set efficiency standard of 80/80; (2) Compare learning achievement before and after the study; and (3) Study the satisfaction of learning activities. Thirty-two sample were the Matthayomsuksa 3 Students, Ramkhamhaeng University Demonstration School (Secondary Division) in the second semester of 2020 academic year, which selected by cluster random sampling from 8 classes. The research instruments were 5 learning activity packages, 1 test of 35 items, and a satisfaction questionnaire form. The data were analyzed by the percentage, mean, standard deviation, and t-test for dependent. The research results were found that: (1) The efficiency of learning activity packages passed the criteria at the 86.46/88.57 level which was higher than criteria. (2) After the completion of the study, the students’ learning achievement was significantly higher than before at the statistically significant level of .01. (3) The overall satisfaction with the learning activities was at the high level ( = 4.16, S.D. = 0.84).